Menjembatani Digital Divides: Pergeseran Pola Pikir Facebook-Commerce - Muhammad Rahel, Izzatun Maghfirah, Nina Kholifah, (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
The mediating impact of customer satisfaction on the influence of utilitarian value on word of mouth is the aim of this analysis. This research was conducted on Facebook users (Nina Fashion accounts) who carried out online transactions (Facebook commerce). Social research with a quantitative paradigm is the method used in this research. This type of research is explanatory (explanatory research). The population in this research are all consumers who have purchased Nina fashion products with at least one purchase transaction or more, totaling 550 people, and the sample used in this research was 95 people, with the analytical tool used being the Structure Equation Model (SEM) . The results of this research reveal that the influence of the Utilitarian Value variable (X) on the Customer Satisfaction variable (Z) has a positive and significant effect with an estimated value of 61.4%. The influence of the Utilitarian Value (X) variable on the Word of Mouth (Y) variable has a positive and significant effect with an estimated value of 38.2%. The influence of the Customer Satisfaction variable (Z) on the Word of Mouth variable (Y) has a positive and significant effect with an estimated value of 36.1%. The indirect effect of Utilitarian Value (X) on the Word of Mouth variable (Y) through the Customer Satisfaction variable (Z) is not significant and positive with an estimated value of 7.4%. Indirect influence